2015
DOI: 10.1128/jvi.02705-14
|View full text |Cite
|
Sign up to set email alerts
|

AP-2-Associated Protein Kinase 1 and Cyclin G-Associated Kinase Regulate Hepatitis C Virus Entry and Are Potential Drug Targets

Abstract: Hepatitis C virus (HCV) enters its target cell via clathrin-mediated endocytosis. AP-2-associated protein kinase 1 (AAK1) and cyclin G-associated kinase (GAK) are host kinases that regulate clathrin adaptor protein (AP)-mediated trafficking in the endocytic and secretory pathways. We previously reported that AAK1 and GAK regulate HCV assembly by stimulating binding of the subunit of AP-2, AP2M1, to HCV core protein. We also discovered that AAK1 and GAK inhibitors, including the approved anticancer drugs suniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(172 citation statements)
references
References 114 publications
8
155
0
Order By: Relevance
“…As shown in Fig. 3E, protein levels of Nkx3.2 in human primary chondrocytes were significantly augmented by administering IPA-3, a PAK1 inhibitor [58]. In addition, as seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Fig. 3E, protein levels of Nkx3.2 in human primary chondrocytes were significantly augmented by administering IPA-3, a PAK1 inhibitor [58]. In addition, as seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has been shown that depletion of GAK by siRNA is dispensable for HCV RNA replication, but significantly inhibits two temporally distinct steps of the HCV life cycle: entry and assembly. 19,20 Similarly, pharmacological inhibitors of the kinase activity of GAK disrupted HCV entry and assembly, thereby further validating GAK as a potential antiviral target. Erlotinib (Figure 1), an approved anticancer drug that potently inhibits GAK as an off-target effect, effectively disrupted HCV entry and assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Erlotinib (Figure 1), an approved anticancer drug that potently inhibits GAK as an off-target effect, effectively disrupted HCV entry and assembly. 19,20 Moreover, we recently reported the discovery of isothiazolo[4,3- b ]pyridines as a class of selective GAK inhibitors that are structurally unrelated to erlotinib. 21 The most potent compounds, 1 and 2, were endowed with Kd values of 8.3 and 8.9 nM, respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was no difference between the wild-type virus and the W420 mutants. The main target of erlotinib is EGFR; however, Neveu et al recently reported that erlotinib also inhibits cyclin G-associated kinase (GAK) during HCV entry (63). GAK is a regulator of clathrin-mediated endocytosis that recruits clathrin and AP-2 to the plasma membrane.…”
Section: E2 Mutations Alter Virus-receptor Interactionsmentioning
confidence: 99%
“…The host cell kinase AP-2-associated protein kinase 1 (AAK1) is a second regulator of AP-2 clathrinmediated endocytosis. AAK1 was also shown to regulate EGFRmediated HCV entry (63). Therefore, we used sunitinib, a kinase inhibitor that targets AAK1, to investigate if the W420 mutants require AAK1.…”
Section: E2 Mutations Alter Virus-receptor Interactionsmentioning
confidence: 99%